2016
DOI: 10.13005/bbra/2077
|View full text |Cite
|
Sign up to set email alerts
|

An Up-to-Date Review of Phytochemicals and Biological Activities in Chrysanthemum spp

Abstract: The Chrysanthemum is a well-known traditional Chinese medicinal herb which has been used as a drug for thousands of years. From the detailed literature survey it is determined that the dried flowers of Chrysanthemum contain organic groups such as alkanes, flavonoids, terpinoids, unsaturated fatty acids and polysaccharides which belongs to Secondary constituents in Phytochemicals classification. The knowledge and analysis of bioactive compounds present in the Chrysanthemums can be used for next generation drug … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
(23 reference statements)
1
7
0
Order By: Relevance
“…A second study found that the flowers of Ch. coronarium were rich in luteolin ( 170 ), whereas the leaves were high in rutin ( 176 ) [ 175 ]. Acacetin-7- O -galacturonide (3) as well as nine other known compounds including a flavonol, kaempferol ( 177 ); a flavonone, eriodictyol ( 178 ); four flavones, acacetin ( 179 ), apigenin ( 180 ), 6-methoxy-apigenin ( 181 ) (hispidulin), luteolin ( 170 ); and three glycosides, apigenin-7- O -glucoside ( 182 ), kaempferol-3- O -rutinoside ( 183 ), and luteolin-7- O -glucoside ( 184 ) were identified from O. alexandrinum flowers [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A second study found that the flowers of Ch. coronarium were rich in luteolin ( 170 ), whereas the leaves were high in rutin ( 176 ) [ 175 ]. Acacetin-7- O -galacturonide (3) as well as nine other known compounds including a flavonol, kaempferol ( 177 ); a flavonone, eriodictyol ( 178 ); four flavones, acacetin ( 179 ), apigenin ( 180 ), 6-methoxy-apigenin ( 181 ) (hispidulin), luteolin ( 170 ); and three glycosides, apigenin-7- O -glucoside ( 182 ), kaempferol-3- O -rutinoside ( 183 ), and luteolin-7- O -glucoside ( 184 ) were identified from O. alexandrinum flowers [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Flavonoids luteolin-7-O-glucuronide (169), luteolin (170), quercetin-3-O-rhamnogalactoside (171), and quercetin-7-O-glucoside (172) were identified in the leaves of Ch. coronarium; luteolin-4 ′ -methyl ether (173), quercetin (174), and quercetin-3-O-rhamnosyl (175) were identified in the flowers [151]. A second study found that the flowers of Ch.…”
Section: • Flavonoidsmentioning
confidence: 97%
“…Chrysanthemum (Chrysanthemum indicum L.) is a perennial herbaceous plant belonging to the Compositae family of short-day plants. It renews its cultivation annually and is believed to have originated in China, where it has been cultivated for over 2000 years (Chae, 2016). This plant stands out by blooming when other flowers in the garden are scarce, reaching its peak production in the fall, earning it the title "Autumn Monarch" (Senapati et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Anwar ul Haq 1 , Maqsooda Parveen 2 , Shehzadi Saima 3 * and Khalid Masood Ahmad 1 * the international and national trade for worshipping and for making garlands (Mamta and Ajit, 2014). The bioactive compounds in chrysanthemum are being used in drug development process (Chae, 2016). Due to low in calories, chrysanthemum tea is also excellent for overweight people.…”
Section: Introductionmentioning
confidence: 99%